THE PROFESSIONALISM OF DOCTOR THROUGH THE LANGUAGE POLITENESS: PRAGMATICS STUDIES - Aprili Yanti (Journal MELT (Medium for English Language Teaching), 2018)
The ability to speak is one of the language skills that a person needs, especially students as prospective scientists. This ability is not a capability inherited from generation to generation even though basically humans can talk scientifically. However, formal speaking skills require intensive training and direction or guidance (see Arsjad and Mukti, 1988: 1). Patients are encouraged to choose a doctor general or family doctor who can give a sense of trust, feel comfortable tell his health problems and undergo an examination, then answer all questions asked by patients and explain it in layman, too give enough time for it all.By having patient-doctor relationships good, patients can get degrees optimal health, health services efficient, & prevent mistakes in unnecessary treatment.Some of the factors underlying language politeness are namely social distance between speakers and speakers, has differences in terms of age and sociocultural / professional background, religion etc.